SEMANGAT KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT LUBUK BATANG KABUPATEN OGAN KOMERING ULU (OKU) - Weni Agustina; Novie Al Muhariah; Darman Syafeâ€™i (Ekonomika, 2025)
This research discusses the influence of work enthusiasm and work motivation on employee performance att he Lubuk Batang District Office,Ogan Komering Ulu Regency (OKU). The population in this study consists of 35 employees at the Lubuk Batang District Office, and the data collection technique used is the distribution of questionnaires. The analysis method is using multiple linear regression, as well as t-tests and f-tests.The results of the analysis show that the t-values for the variables of work enthusiasm (X1) and work motivation (X2), indicating that both variables have a partial effect on employee performance at the Lubuk Batang District Office, Ogan Komering Ulu Regency (OKU). Simultaneously, work enthusiasm (X1) and workmotivation (X2) have a significant effect on employeeperformance. The coefficient of determination (RÂ²)is 0.972, meaning that thecontribution ofwork enthusiasm and work motivation to employee performance is 97.2%, while the remaining 2.8% is influenced by other variables not mentioned in this study, such as individual factors, psychological factors, and organizational factors